Oxygen reduction reaction mechanism on a phosporus-doped pyrolyzed graphitic Fe/N/C catalyst - Hermawan K. Dipojono, .- (Royal Society of Chemistry, 2019)
The oxygen reduction reaction (ORR) mechanism on the active sites of a phosphorus-doped pyrolyzed Fe/N/C catalyst is examined by using density functional theory based calculations. The introduction of the phosphorus dopant creates three initial possible active sites for the ORR i.e., FeN4, C–N and P-doped sites. In the presence of O2, the P-doped sites become passivated while the rest of the catalyst sites are still functional. The ORR profile for the associative mechanism (the O2 molecule is reduced from its molecular form) on the FeN4 site is practically unaffected by the presence of the neighboring P[double bond, length as m-dash]O site. However, the ORR profile for the dissociative mechanism (the O2 molecule is reduced from its dissociated form) on the FeN4 site is significantly improved as compared to that on the undoped Fe/N/C catalyst system. This phenomenon is mainly induced by the distortion of C–C networks due to the presence of the neighboring FeN4 and P[double bond, length as m-dash]O sites, which leads to the stabilization of the *OH adsorption state on the C atoms next to the FeN4 site.